2017
DOI: 10.1016/j.imu.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

EEG signal classification using PSO trained RBF neural network for epilepsy identification

Abstract: The electroencephalogram (EEG) is a low amplitude signal generated in the brain, as a result of information flow during the communication of several neurons. Hence, careful analysis of these signals could be useful in understanding many human brain disorder diseases. One such disease topic is epileptic seizure identification, which can be identified via a classification process of the EEG signal after preprocessing with the discrete wavelet transform (DWT). To classify the EEG signal, we used a radial basis fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(23 citation statements)
references
References 41 publications
0
22
0
1
Order By: Relevance
“…For a given policy, the Bellman expectation equation is used to estimate the state-value function in some simple cases, which is mathematically explained in Eq. (5).…”
Section: Neural Network With Reinforcement Qlearningmentioning
confidence: 99%
See 1 more Smart Citation
“…For a given policy, the Bellman expectation equation is used to estimate the state-value function in some simple cases, which is mathematically explained in Eq. (5).…”
Section: Neural Network With Reinforcement Qlearningmentioning
confidence: 99%
“…The manual practice is rapidly overcome by using the digitization of clinical procedure in the medical domain. Nowadays, medical specialists consider the promising application like Computer Aided Diagnosis (CAD) due to early processing and their effective handling of identification of diseases, however it is facing several challenges [4,5]. But, the important issue is to handle the appropriate medical records, which will help the doctors and technologist to predict the diseases rapidly and further proceed for a speedy recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier research by Hans Berger has shown that there are frequency bands highly connected with the activity of the brain [2]. These frequency bands were named delta (< 4 Hz), theta (4-7 Hz), alpha (8)(9)(10)(11)(12)(13)(14)(15), beta (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31), and gamma (> 32 Hz). The original EEG signal is the compilation of all neuron's activities.…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of NN depends on its topology and the quality of input data. Currently, there are many results from multichannel EEG mapping, where spatial and temporal data of EEG signals are studied, mainly for applications in neurology [19][20][21]. One of the good examples may be the work of Jiao et al In which the pattern recognition methods were used to classify EEG signals coming from working memory during cognitive tasks [22].…”
Section: Introductionmentioning
confidence: 99%
“…An improved RBFNN with gravitation search algorithm is proposed to predict network traffic which has perfect prediction accuracy [18]. In addition, the RBFNN is also used to increase the visibility of image [19] and classify the clinical medical signals for helping doctor identify the diseases [20,21]. A prediction method based on RBFNN carries out not only the optimization of the microstrip line geometrical dimensions, but also characterization processes [22].…”
Section: Introductionmentioning
confidence: 99%